CLUSTERIZATION IN GLOBAL SUPPLY CHAIN MANAGEMENT (Development Service Industry Management, 2023)
The article is devoted to the study of the problem of the possibility of forming global supply chains on the basis of clustering. An overview of various spheres of life where clustering approaches are used was carried out, while the field of logistics was singled out and it was noted that by uniting organizations of different forms of ownership and services, a unique environment is created that maximizes the efficiency of logistics operations and promotes flexibility in solving logistics tasks. Attention is focused on the fact that seaports can act as supporting facilities in the provision of service and other services in global supply chains. It has been proven that the crucial importance in building effective supply chains based on clustering is the provision of continuous cargo flows through the full network integration of the involved participants and objects of the logistics infrastructure on the basis of clustering and a single partner space. It is noted that clustering, unlike other organizational forms of management, unites the efforts of government, business and science according to the principle of territorial localization. The general requirements for clusters have been expanded to cover the issues of overcoming administrative and logistical barriers to the implementation of international transport operations during customs clearance, as well as promoting partnership between suppliers using advanced information technologies. Attention is focused on the similarity of the requirements for the clustering of the port industry with the indicators analyzed in the Logistics Performance Index (LPI). An overview of the 2023 LPI results is presented and it is established that the focus of international trade has shifted from China to India and directly to the port of Singapore. It is proposed to consider the possibility of forming an international port cluster directly on the basis of the leading international port of Singapore. The importance of digitalization for the basis of the formation of clusters on the basis of seaports in order to increase the flexibility and sustainability of supply chains is highlighted.
Keywords: ports; clustering; port cluster; supply chains; international transportation; globalization; infrastructure